Leadership, communication, dan division of labour terhadap employee performance - Sari, Widya Tanjung; Panglipursari, Dwi Lesno (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2022)
This study aims to examine and analyze the effect of leadership, communication, and division of labor on employee performance. In this study using saturated sampling, saturated sampling is a sampling technique when all members of the population are used as samples. The sample in this study were 80 employees. Data analysis was performed using SPSS. Based on the results of data analysis using the t test, it is known that partially leadership, communication, and division of labor have a significant effect on employee performance. Meanwhile, simultaneous testing (F test) was found to have a significant effect on employee performance.